Preliminary validation study of the intrinsic religious motivation scale and the centrality of religiosity scale for the portuguese population - Araújo, Pedro (2021)
Religion is a construct widely present in most people’s lives. Religious motivations, either intrinsic or extrinsic, as well as religious centrality, are crucial aspects of religion. In the Portuguese population, there are no validated instruments to assess these aspects of religion. Accordingly, this study intends to validate the Intrinsic Religious Motivation Scale (IRMS) and the Centrality of Religiosity Scale (CRS) for the Portuguese population. This is a validation study whose sample consists of 326 participants (73.1% women) from the general population. Exploratory and confirmatory factor analyses were carried out and the correlations between the constructs and self-compassion were determined to assess the convergent and divergent validity. The results obtained confirm the existence of models adjusted to the population, allowing us to conclude that the instruments are reliable for assessing the studied constructs. The validation of the IRMS and CRS for the Portuguese population is of outstanding importance, as it provides researchers in the field with valid instruments and psychometric qualities to carry out research within religion and religiosity.